Chemically derived graphene : functionalization, properties and applications - Zhang, Jintao (Royal Society of Chemistry, 2018)
A comprehensive overview of the recent and state-of-the-art research on chemically derived graphene materials for different applications.
Includes index.
Keywords: Graphene.; elektronické knihy; electronic books